2020
DOI: 10.1007/s42452-020-03375-w
|View full text |Cite|
|
Sign up to set email alerts
|

Example-dependent cost-sensitive credit cards fraud detection using SMOTE and Bayes minimum risk

Abstract: This paper presents fraud detection problem as one of the most common problems in secure banking research field, due to its importance in reducing the losses of banks and e-transactions companies. Our work will include: applying the common classification algorithms such as logistic regression (LR), random forest (RF), alongside with modern classifiers with state-of-the-art results as XGBoost (XG) and CatBoost (CB), testing the effect of the unbalanced data through comparing their results with and without balan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…Other scholars have assessed the likelihood of vulnerability to different types of financial crime by applying computational and statistical methods [ 12 , 59 ]. The two most common techniques are neural networks [ 49 , 60 ] and binary logistic regression, respectively [ 41 , 50 , 61 , 62 ]. Neural networks could effectively be employed to identify patterns in large unstructured datasets [ 12 , 58 , 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other scholars have assessed the likelihood of vulnerability to different types of financial crime by applying computational and statistical methods [ 12 , 59 ]. The two most common techniques are neural networks [ 49 , 60 ] and binary logistic regression, respectively [ 41 , 50 , 61 , 62 ]. Neural networks could effectively be employed to identify patterns in large unstructured datasets [ 12 , 58 , 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…Besides, using over-sampling methods leads to the production of duplicate data that doesn't provide information (the data and information are different, and the subject is discussed under the "Entropy"). Some researchers use synthetic minority oversampling (SMOTE) as a solution, which avoids the drawbacks of under and over sampling [5], [17], [22]. However, the SMOTE method causes an increase in the false-positive rate, which is not acceptable in banking for customer orientation.…”
Section: B Data Pre-processingmentioning
confidence: 99%
“…However, the SMOTE method causes an increase in the false-positive rate, which is not acceptable in banking for customer orientation. To solve this problem, in this study, we use class weight tuning hyperparameter to solve the mentioned disadvantages [5], [17], [22]. However, the SMOTE method causes an increase in the false-positive rate, which is not acceptable in banking for customer orientation.…”
Section: B Data Pre-processingmentioning
confidence: 99%
“…The oversampling approach can be used to sample imbalanced data by generating new positive samples or replicating some positive samples, such as random oversampling and the synthetic minority oversampling technique (SMOTE; Chawla et al, 2002). Almhaithawi et al (2020) applied four common classifiers with SMOTE for fraud detection and concluded that SMOTE could improve the performance of most classifiers. The undersampling approach can be used to sample imbalanced data by eliminating some negative samples or generating new negative samples to replace the original negative samples, such as BalanceCascade (Liu et al, 2009) and cluster centroids (Lin et al, 2017).…”
Section: A Learning From Imbalanced Datamentioning
confidence: 99%